(untitled) (LACCEI, 2024)
: The scientific and technological progress resulting from globalization made industrial companies seek to obtain higher quality, productivity, costs, technology in their processes and delivery of their products and services that they offered, complying with international standards that allowed them to be more competitive. The steel companies have been evolving and the manufacture of steel is part of the economic growth of the country, through a process of high technological level, the steel mills are the protagonists of this rebirth of steel and after a process of hot mechanical deformation the bars are obtained construction that are used for the manufacture of buildings, transport bridges, infrastructures, among others. Within the process, premature wear of channels of the rolling cylinder was identified, causing daily stops to change channels in the rolling stand For this reason, the refrigeration system must be redesigned to prolong the useful life of the rolling cylinders, improving productivity, reducing downtime, minimizing unsafe conditions for employees and reducing waste in water resources